Analisis Kemampuan Literasi Digital Mahasiswa dalam Mendukung Menulis Karya Ilmiah di Politeknik Negeri Lampung - Upy Raudotul Jannah; Maisuri Hardani; Gilang Zulfikar (Academy of Education Journal, 2026)
Having digital literacy skills can support the writing of scientific papers to be more qualified. Various technical matters are sometimes often underestimated such as wasted time tidying up the position of paragraphs, difficulty finding reference sources, difficulty processing data using basic software. Difficulty compiling bibliographies automatically and so on. This is what actually backfires on technological developments. Instead of facilitating the process of writing scientific papers, it complicates the process. Therefore, the author analyzes the extent of students' skills in mastering digital skills to support writing papers. The purpose of this study is to analyze students' digital literacy skills reviewed from eight aspects, functional skills, creativity, collaboration, communication, the ability to select information, critical thinking, socio-cultural understanding, and data security. The method used is quantitative descriptive research. The results of this study indicate that students still face several obstacles, especially in creativity, sorting information, critical thinking, and data security. This causes the scientific papers produced to be less than good. With digital literacy in students, there will be a positive impact to facilitate the process of writing scientific papers. Digital literacy training and familiarization are needed to ensure students are able to optimally utilize digital literacy to improve the quality of their scientific work.